Effect of Water Absorption on impact strength of synthetic fibers with Epoxy-unsaturated polyester blends - Dheya , Balkees M.; Ameen, Mustafa H. (Iraqi Journal of Science, 2022)
In this study a composite materials were prepared containing matrix of polymer blend (Epoxy (EP) 90% + unsaturated polyester (UPS) 10%), (Epoxy (EP) 80% + unsaturated polyester (UPS) 20%), reinforced with Kevlar (K) or, and iron woven (Fe) with one value of volume fraction (30) %. This composite are from: (EP 90%, UPE 10% +K), (EP 90%, UPE 10% +K+Fe), (EP 80%, UPE 20% +K), (EP 80%, UPE 20% +K+Fe). All samples were prepared using hand layup method and then impact test was done in both normal condition and after immersion in tap water for the same period time (eight weeks) also diffusion test was done for period's time (three months). The results showed that had been effected differently after immersion, but specimen (EP80%+UPS20%+K+Fe) had superior values of impact strength in normal condition and after immersion in tap water also diffusion test that the binary blend, EP (80%) +UPE (20%) reinforced with Kevlar and iron woven gives a highest values of diffusivity in the tap water.